Cold-pressing adhesive for fireproof door and preparation method of cold-pressing adhesive

By selecting a suitable combination of castor oil and polyether polyol and adding specific additives to form a cold pressed glue suitable for bonding between different substrates, the problem of poor bonding strength between substrates in the prior art is solved, and the problem of poor bonding strength between substrates is achieved High strength and efficient processing bonding effect.

CN119410325APending Publication Date: 2025-02-11SHANGHAI JINQIANG ADHESIVE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411852743.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The bonding strength of existing cold pressed glues between different substrates is poor, especially the bonding effect between polymer materials, metals, paper and wood is not ideal.

Method used

By selecting a combination of castor oil and polyether polyol, the system viscosity is regulated, and silica, inorganic filler, plasticizer and silane coupling agent are added to form a cold pressed glue of components A and components B.

Benefits of technology

It realizes high-strength bonding between different substrates, improves the activity period and opening time of the glue, enhances the processing performance, and improves the shear strength, and is suitable for the preparation of fireproof doors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410325A_ABST
    Figure CN119410325A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, in particular to a cold-pressing adhesive for a fireproof door and a preparation method of the cold-pressing adhesive. Comprising a component A and a component B. The component A comprises, by weight, 100-200 parts of castor oil, 50-100 parts of polyether polyol, 150-250 parts of an inorganic filler, 10-40 parts of a plasticizer, 0.1-2 parts of an antifoaming agent, 1-5 parts of silicon dioxide and 0.5-5 parts of a silane coupling agent, and the component B comprises an isocyanate curing agent. The adhesive is applied to bonding of fireproof doors (color plates and paper honeycombs), and has excellent bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and more specifically to a cold-pressed adhesive for fire doors and a preparation method thereof. Background Art

[0002] Cold-pressed adhesive is a kind of adhesive product with the characteristics of fast curing, strong adhesion, environmental safety and easy use, which can be widely used in the bonding and production of various materials. However, the existing cold-pressed adhesive has the problem of poor bonding strength between different substrates, such as polymer materials, metals, paper, wood, etc.

[0003] Chinese invention patent CN107384258A discloses a cold-pressed adhesive and its preparation method, which is composed of the following components in mass percentage: 90% VAE emulsion, 9% water-based polyurethane emulsion, 0.5% defoamer, and 0.5% preservative. It can achieve ultra-fast curing and has higher bonding strength than ordinary cold-pressed adhesives, but the cold-pressed adhesive is only suitable for bonding between woods and does not involve research on bonding between different substrates. Summary of the invention

[0004] The first aspect of the present invention provides a cold-pressed adhesive for fire doors, comprising a component A and a component B, wherein the component A comprises, by weight, 100-200 parts of castor oil, 50-100 parts of polyether polyol, 150-250 parts of inorganic filler, 10-40 parts of plasticizer, 0.1-2 parts of defoamer, 1-5 parts of silicon dioxide and 0.5-5 parts of silane coupling agent, and the component B comprises an isocyanate curing agent.

[0005] Preferably, the component A comprises, by weight: 150 parts of castor oil, 50-100 parts of polyether polyol, 150-250 parts of inorganic filler, 10-40 parts of plasticizer, 0.1-2 parts of defoamer, 1-5 parts of silicon dioxide and 0.5-5 parts of silane coupling agent.

[0006] Preferably, the isocyanate curing agent includes a diisocyanate curing agent.

[0007] Further preferably, the diisocyanate curing agent includes at least one of diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4′-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, norbornane diisocyanate, cyclohexane dimethylene diisocyanate, phenylmethylene diisocyanate, toluene-2,4-diisocyanate and polydiphenylmethane diisocyanate.

[0008] More preferably, the diisocyanate curing agent includes diphenylmethane diisocyanate.

[0009] Preferably, the castor oil comprises refined first-grade castor oil.

[0010] The hydroxyl value of the polyether polyol is 260-420 mgKOH / g.

[0011] Preferably, the hydroxyl value of the polyether polyol is 300-400 mgKOH / g.

[0012] More preferably, the hydroxyl value of the polyether polyol is 300-350 mgKOH / g. The present application study found that by selecting a combination of castor oil and polyether polyols, the viscosity of the system (25°C) can be controlled within the range of 20,000-28,000 mPa·s, meeting the requirements of cold pressing at room temperature. In particular, the selection of a polyether polyol compound with a hydroxyl value of 260-420 mgKOH / g can increase the activity period and open time of the glue at an appropriate viscosity, thereby improving the processing performance. This may be due to the entanglement between the long-chain structures of castor oil and polyether polyols, which reduces the probability of collision between the hydroxyl group and the isocyanate group in the curing agent.

[0013] The content of silicon dioxide in component A is greater than 0.4 wt %.

[0014] Preferably, the content of silicon dioxide in component A is 0.4-2wt%.

[0015] Further preferably, the content of silicon dioxide in component A is 0.4-1 wt %.

[0016] The silicon dioxide comprises a specific surface area of ​​100-200m 2 / g of fumed silica.

[0017] Preferably, the silicon dioxide comprises a specific surface area of ​​100-200m 2 / g of hydrophilic fumed silica.

[0018] As an example, the specific surface area of ​​the hydrophilic fumed silica may be: 100 m 2 / g, 130m 2 / g, 150m 2 / g, 170m 2 / g, 180m 2 / g, 190m 2 / g or 200m 2 / g.

[0019] The present application has found that the content of silicon dioxide in component A is greater than 0.4wt%, which can improve the thickening effect and increase the viscosity of the glue, especially when the specific surface area is 100-200m 2 / g of fumed silica can improve the shear strength of the glue. It may be that the small size and large specific surface area of ​​fumed silica particles enable them to more effectively fill the gaps between the long-chain structures of castor oil and polyether polyols, forming a tighter structure. At the same time, the silanol groups on its surface form hydrogen bonds and van der Waals forces with polymer molecules, enhancing the interaction between particles and polymers, thereby improving the strength of the adhesive.

[0020] The inorganic filler includes at least one of active calcium carbonate, light calcium carbonate, heavy calcium carbonate, titanium dioxide, zinc oxide and silicon powder.

[0021] Preferably, the inorganic filler comprises activated calcium carbonate and heavy calcium carbonate, and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:(15-25).

[0022] Further preferably, the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:(17-22).

[0023] The particle size of the inorganic filler is 700-900 meshes.

[0024] As an example, the particle size of the inorganic filler may be 700 mesh, 750 mesh, 800 mesh, 850 mesh or 900 mesh.

[0025] The research of this application found that the inorganic filler selected active calcium carbonate and heavy calcium carbonate, the weight ratio of active calcium carbonate and heavy calcium carbonate is 1: (15-25) and the particle size is 700-900 mesh, which can reduce the production cost and increase the shear strength to more than 4MPa. The addition of heavy calcium carbonate can play a role in strengthening and toughening, but as the amount of heavy calcium carbonate added increases, it is easy to cause the force between molecular chains to decrease, limiting the addition of fillers. By compounding with a specific ratio of active calcium carbonate, it has higher activity, and the specific particle size helps to disperse the two in the system, and can better interact with other components in the adhesive.

[0026] The plasticizer comprises dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:(0.2-0.8).

[0027] Preferably, the weight ratio of dibutyl phthalate to dioctyl phthalate is 1:(0.2-0.6).

[0028] Further preferably, the weight ratio of dibutyl phthalate to dioctyl phthalate is 1:(0.4-0.6).

[0029] This application study found that the weight ratio of dibutyl phthalate to dioctyl phthalate is 1: (0.2-0.6), which can improve the bonding performance of glue in the preparation process of fire doors, especially the bonding between color steel plate and paper honeycomb, on the basis of increasing the active period and open time. The compounding of castor oil and polyether polyol will cause compatibility problems to a certain extent, thereby reducing the mobility of molecular weight, and specific plasticizers are inserted between the molecular chains of polymer compounds, weakening the interaction between molecular chains, matching the polarity between color steel plate and paper honeycomb, and at the same time playing a role in increasing the mobility of molecular chains.

[0030] The silane coupling agent includes bisaminosilane.

[0031] Preferably, the bisaminosilane includes at least one of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792), N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (KH-602), and bisaminosilane oligomer (DH2776).

[0032] Further preferably, the bisaminosilane includes at least one of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792) and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (KH-602).

[0033] The present study found that the selection of bisaminosilane as a silane coupling agent can further improve the bonding strength of the glue and increase the shear strength to above 4.5 MPa, which may be due to the increased compatibility with the system and the increased collision between the active sites that react with the isocyanate group.

[0034] The defoaming agent includes an organosilicon defoaming agent.

[0035] Preferably, the organosilicon defoaming agent includes at least one of trimethyl silicone oil, dimethyl polysiloxane, silicone paste and polysiloxane.

[0036] Further preferably, the organosilicon defoamer comprises polysiloxane.

[0037] A second aspect of the present invention provides a method for preparing a cold-pressed adhesive for a fire door, comprising the following steps: S1, mixing castor oil, polyether polyol and silicon dioxide uniformly; S2, add inorganic filler, vacuum and stir evenly; S3, adding plasticizer, defoamer and silane coupling agent and stirring evenly to obtain component A; S4, prepare component B.

[0038] Beneficial Effects 1. By selecting a combination of castor oil and polyether polyols, the system viscosity (25°C) can be controlled at 20,000-28,000 mPa·s, meeting the use requirements of cold pressing at room temperature. In particular, by selecting a polyether polyol with a hydroxyl value of 260-420 mgKOH / g, the activity period and open time of the glue can be increased at a suitable viscosity, thereby improving the processing performance.

[0039] 2. The content of silicon dioxide in component A is greater than 0.4wt%, which can improve the thickening effect and increase the viscosity of the glue, especially when the specific surface area is 100-200m 2 / g of fumed silica can increase the shear strength of the glue to 4MPa.

[0040] 3. The inorganic fillers are selected from activated calcium carbonate and heavy calcium carbonate, the weight ratio of which is 1: (15-25) and the particle size is 700-900 mesh, which can reduce the production cost and increase the shear strength to 4.2 MPa.

[0041] 4. The weight ratio of dibutyl phthalate to dioctyl phthalate is 1: (0.2-0.6), which can improve the bonding performance of glue in the preparation process of fire doors on the basis of increasing the active period and open time, especially suitable for the bonding between color steel plates and paper honeycombs.

[0042] 5. The silane coupling agent is bisaminosilane, which can further improve the bonding strength of the glue and increase the shear strength to 4.6MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is the material breaking effect of the glue prepared by the formula of Example 1.

[0044] Figure 2 This is the material breaking effect of the glue prepared by the formula of Comparative Example 1.

[0045] Figure 3 This is the material breaking effect of the glue prepared by the formula of Comparative Example 2.

[0046] Figure 4 This is the material breaking effect of the glue prepared by the formula of Comparative Example 8.

[0047] Figure 5 This is the material breaking effect of the glue prepared by the formula of Example 2.

[0048] Figure 6 This is the material breaking effect of the glue prepared by the formula of Example 3.

[0049] Figure 7 This is the material breaking effect of the glue prepared by the formula of Example 4. DETAILED DESCRIPTION

[0050] Example 1 A cold-pressed adhesive for fire doors, consisting of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 200 parts by weight of inorganic filler, 18 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0051] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0052] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:19.

[0053] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:0.5.

[0054] A preparation method of cold-pressed adhesive for fire doors: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0055] Example 2 A cold-pressed adhesive for fire doors, consisting of component A and component B, wherein component A is composed of 200 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 50 parts by weight of polyether polyol, 250 parts by weight of inorganic filler, 40 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0056] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0057] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:24.

[0058] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:0.5.

[0059] A preparation method of cold-pressed adhesive for fire doors: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0060] Example 3 A cold-pressed adhesive for fire doors, consisting of component A and component B, wherein component A is composed of 200 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 50 parts by weight of polyether polyol, 250 parts by weight of inorganic filler, 10 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0061] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0062] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:24.

[0063] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:0.5.

[0064] A preparation method of cold-pressed adhesive for fire doors: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0065] Example 4 A cold-pressed adhesive for fire doors, composed of component A and component B, wherein the component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 260 parts by weight of inorganic filler, 10 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and the component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0066] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0067] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:15.

[0068] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:0.5.

[0069] A preparation method of cold-pressed adhesive for fire doors: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0070] Comparative Example 1 A cold-pressed adhesive, composed of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 200 parts by weight of inorganic filler, 18 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0071] The polyether polyol has a hydroxyl value of 440-460 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., DV-125.

[0072] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:19.

[0073] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:0.5.

[0074] A preparation method of cold pressed adhesive: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0075] Comparative Example 2 A cold-pressed adhesive, composed of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 200 parts by weight of inorganic filler, 18 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0076] The polyether polyol has a hydroxyl value of 225-255 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-700.

[0077] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:19.

[0078] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:0.5.

[0079] A preparation method of cold pressed adhesive: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0080] Comparative Example 3 A cold-pressed adhesive, composed of component A and component B, wherein the component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 200 parts by weight of inorganic filler, 18 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 1 part by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and the component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0081] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0082] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:19.

[0083] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:0.5.

[0084] A preparation method of cold pressed adhesive: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0085] Comparative Example 4 A cold-pressed adhesive, composed of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 200 parts by weight of inorganic filler, 18 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0086] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0087] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 600 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:19.

[0088] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:0.5.

[0089] A preparation method of cold pressed adhesive: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0090] Comparative Example 5 A cold-pressed adhesive, composed of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 200 parts by weight of inorganic filler, 18 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0091] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0092] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 1000 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:19.

[0093] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:0.5.

[0094] A preparation method of cold pressed adhesive: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0095] Comparative Example 6 A cold-pressed adhesive, composed of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 200 parts by weight of inorganic filler, 18 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0096] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0097] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:19.

[0098] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:1.

[0099] A preparation method of cold pressed adhesive: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0100] Comparative Example 7 A cold-pressed adhesive, composed of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 200 parts by weight of inorganic filler, 18 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0101] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0102] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:19.

[0103] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:2.

[0104] A preparation method of cold pressed adhesive: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0105] Comparative Example 8 A cold-pressed adhesive, composed of component A and component B, wherein the component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 200 parts by weight of inorganic filler, 18 parts by weight of plasticizer (dibutyl phthalate), 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-792), and the component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0106] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0107] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:19.

[0108] A preparation method of cold pressed adhesive: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0109] Comparative Example 9 A cold-pressed adhesive, composed of component A and component B, wherein component A is composed of 150 parts by weight of castor oil (Nantong Yingguan New Materials, refined first-grade castor oil), 80 parts by weight of polyether polyol, 200 parts by weight of inorganic filler, 18 parts by weight of plasticizer, 0.5 parts by weight of defoamer (Xingrui, SGR1832), 2 parts by weight of silicon dioxide (Hubei Huifu Nanomaterials Co., Ltd., HL-150) and 1.5 parts by weight of silane coupling agent (United Silicon Chemical, KH-540), and component B is an isocyanate curing agent (diphenylmethane diisocyanate, Wanhua WANNATE PM-130).

[0110] The polyether polyol has a hydroxyl value of 330-350 mgKOH / g and is purchased from Guangzhou Fufei Chemical Technology Co., Ltd., MN-500.

[0111] The inorganic filler is activated calcium carbonate (Helixin, 800 mesh) and heavy calcium carbonate (Guangxi Wowu, 800 mesh), and the weight ratio of the activated calcium carbonate to the heavy calcium carbonate is 1:19.

[0112] The plasticizers are dibutyl phthalate and dioctyl phthalate, and the weight ratio of the dibutyl phthalate to the dioctyl phthalate is 1:0.5.

[0113] A preparation method of cold pressed adhesive: S1, mix castor oil, polyether polyol and silicon dioxide and stir for 20 minutes at a speed of 800 r / min; S2, add inorganic filler, vacuum and stir for 1h, speed 1300r / min; S3, adding plasticizer, defoamer and silane coupling agent and stirring for 20 minutes at a speed of 1300 r / min to obtain component A; S4, prepare component B.

[0114] Performance testing methods and data Preparation of glue: Component A and component B were mixed in a weight ratio of 100:20, and the following performance tests were performed. The test data are listed in Table 1. The amount of glue applied was 200 g per square meter.

[0115] (1) Tensile shear strength: According to the national standard GB / T7124 / 2008, the test is carried out after curing for 7 days.

[0116] (2) Activity period: According to the national standard GB / T7123.1-2002, after the glue is evenly mixed, if there is obvious resistance when stirring, it is judged that the activity period has ended.

[0117] (3) Open time: After the glue is evenly mixed, it is coated on the surface of the substrate (aluminum sheet). When the state of the glue film changes from wet to brushed state, the open time is judged to be over.

[0118] (4) Viscosity: Tested according to national standard GB / T2794-1995.

[0119] (5) Damage degree of the core material at the bonding point: The glue of Example 1, Comparative Examples 1, 2, and 8 was used to bond the plate, the core material, and the plate together, respectively. The plate was a color steel plate, and the core material was a paper honeycomb. The plate was put into a cold press and cold pressed at 25° C. for 6 h. After the pressure was released and cured for 18 h, one side of the plate was torn open to observe the damage degree of the core material at the bonding point. The damage degree was evaluated by scoring "high, medium, and low". A high damage rate represents a good bonding effect. The residual area of ​​the core material on the contact surface was divided into "high", "medium", and "low". Specifically, a residual area of ​​not less than 80% is "high", a residual area of ​​50-80% is "medium", and a residual area of ​​less than 50% is "low". Figure 1 , 5 As shown in Figures 6 and 7, the degree of damage to the core material at the bonding point is “high”.

[0120] Table 1 Test items Tensile shear strength MPa Active period min Opening hours Viscosity mPa·s Example 1 4.6 18 73 25000 Example 2 4.4 18 75 25500 Example 3 4.9 16 70 31000 Example 4 4.9 16 70 21000 Comparative Example 1 4.0 15 65 23000 Comparative Example 2 3.8 15 66 26000 Comparative Example 3 4.0 18 73 22000 Comparative Example 4 3.2 14 64 20000 Comparative Example 5 3.6 16 65 28000 Comparative Example 6 3.4 22 77 23000 Comparative Example 7 3.0 25 82 21000 Comparative Example 8 4.0 15 68 26000 Comparative Example 9 4.2 19 75 25000 like Figure 1 , 5 , 6, and 7, the degree of damage to the core material at the bonding point is "high", such as Figure 2-4 As shown, the degree of damage to the core material at the bonding point is "medium". Compared with the preferred embodiment 1, the bonding effects of comparative examples 1, 2, and 8 are all reduced.

Claims

1. A cold-pressed adhesive for fire doors, characterized in that: The invention comprises component A and component B, wherein the component A comprises, by weight, 100-200 parts of castor oil, 50-100 parts of polyether polyol, 150-250 parts of inorganic filler, 10-40 parts of plasticizer, 0.1-2 parts of defoamer, 1-5 parts of silicon dioxide and 0.5-5 parts of silane coupling agent, and the component B comprises an isocyanate curing agent; the plasticizer comprises dibutyl phthalate and dioctyl phthalate, and the weight ratio of dibutyl phthalate to dioctyl phthalate is 1:(0.2-0.8).

2. The cold-pressed adhesive for fire doors according to claim 1, characterized in that: The hydroxyl value of the polyether polyol is 260-420 mgKOH / g.

3. The cold-pressed adhesive for fire doors according to claim 2, characterized in that: The content of silicon dioxide in component A is greater than 0.4 wt %.

4. The cold-pressed adhesive for fire doors according to claim 3, characterized in that: The silicon dioxide comprises a specific surface area of ​​100-200m 2 / g of fumed silica.

5. The cold-pressed adhesive for fire doors according to claim 4, characterized in that: The inorganic filler includes at least one of active calcium carbonate, light calcium carbonate, heavy calcium carbonate, titanium dioxide, zinc oxide and silicon powder.

6. The cold-pressed adhesive for fire doors according to claim 5, characterized in that: The inorganic filler comprises active calcium carbonate and heavy calcium carbonate, and the weight ratio of the active calcium carbonate to the heavy calcium carbonate is 1:(15-25).

7. The cold-pressed adhesive for fire doors according to claim 6, characterized in that: The particle size of the inorganic filler is 700-900 meshes.

8. The cold-pressed adhesive for fire doors according to claim 7, characterized in that: The silane coupling agent includes bisaminosilane.

9. A method for preparing the cold-pressed adhesive for fire doors according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing castor oil, polyether polyol and silicon dioxide uniformly; S2, add inorganic filler, vacuum and stir evenly; S3, adding plasticizer, defoamer and silane coupling agent and stirring evenly to obtain component A; S4, prepare component B.

Citation Information

Patent Citations

  • Cold-pressing glue, preparation method and application of cold-pressing glue

    CN107384258A